THE SCIENCE LABORATORY OF THE FUTURE SCHOOL. EMERGING TECHNOLOGIES AND CONTENT - Kefalis, Chrysovalantis; Stavridis, Sotiris; Drigas, Athanasios (RECIMA21 - Revista Científica Multidisciplinar - ISSN 2675-6218, 2023)
This paper investigates the current trends in the transformation of STEM laboratories in the age of digitization due to the integration of digital technologies and the recognition of the importance of developing metacognitive skills. The paper examines the role of metacognition and its impact on the learning process, as well as the use of digital technologies such as remote labs, virtual labs, augmented reality, virtual reality, and mobile devices in STEM education. Results from this research suggest that the use of these digital technologies can be beneficial for science learning in both higher and secondary education. Additionally, these technologies can be used to promote student engagement, collaboration, and access to scientific knowledge. Furthermore, metacognition is an important skill for both teachers and students, and can be developed through the use of the knowledge pyramid, emotional intelligence pyramid, metacognitive pyramid, and giftedness pyramid models.